An Inorganic/Organic S‐Scheme Heterojunction H2‐Production Photocatalyst and its Charge Transfer Mechanism. Issue 22 (26th April 2021) - Cheng, Chang; He, Bowen; Fan, Jiajie; Cheng, Bei; Cao, Shaowen; Yu, Jiaguo
Abstract: Inspired by natural photosynthesis, constructing inorganic/organic heterojunctions is regarded as an effective strategy to design high‐efficiency photocatalysts. Herein, a step (S)‐scheme heterojunction photocatalyst is prepared by in situ growth of an inorganic semiconductor firmly on an organic semiconductor. A new pyrene‐based conjugated polymer, pyrene‐ alt ‐triphenylamine (PT), is synthesized via the typical Suzuki–Miyaura reactions, and then employed as a substrate to anchor CdS nanocrystals. The optimized CdS/PT composite, coupling 2 wt% PT with CdS, exhibits a robust H2 evolution rate of 9.28 mmol h −1 g −1 with continuous release of H2 bubbles, as well as a high apparent quantum efficiency of 24.3%, which is ≈8 times that of pure CdS. The S‐scheme charge transfer mechanism between PT and CdS, is systematically demonstrated by photoirradiated Kelvin probe measurement and in situ irradiated X‐ray photoelectron spectroscopy analyses. This work provides a protocol for preparing specific S‐scheme heterojunction photocatalysts on the basis of inorganic/organic coupling. Abstract : The construction of a CdS/PT inorganic/organic S‐scheme heterojunction not only leads to efficient charge separation and transfer, but also increased redox ability and enhanced stability for photocatalytic hydrogen evolution.